2007
DOI: 10.2527/jas.2007-0176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin A supplementation in young lambs on performance, serum lipid, and longissimus muscle lipid composition

Abstract: Forty crossbred wethers (BW = 28.7 kg) were used to evaluate the effects on LM lipid composition of diets containing high and low levels of vitamin A. Four treatments arranged as a 2 x 2 factorial with a completely random design were investigated: backgrounding (BG) and finishing (FN) with no supplemental vitamin A (LL); BG with no supplemental vitamin A and FN with high vitamin A (6,600 IU/kg of diet, as fed) supplementation (LH); BG with high vitamin A supplementation and FN with no vitamin A supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Dry Spanish potato vine was the only forage source and the grain sources contained either very low or undetectable carotene. Therefore, the diets were assumed no carotenes derived vitamin A (Arnett et al, 2007).…”
Section: Treatment Of Animalsmentioning
confidence: 99%
“…Dry Spanish potato vine was the only forage source and the grain sources contained either very low or undetectable carotene. Therefore, the diets were assumed no carotenes derived vitamin A (Arnett et al, 2007).…”
Section: Treatment Of Animalsmentioning
confidence: 99%
“…Rats given the cafeteria diet supplemented with a high concentration of vitamin A showed increased adiposity compared with rats given the same diet containing a low amount of vitamin A (Redonnet et al 2008). In young lambs, high levels of vitamin A supplementation led to an increase in the total intramuscular lipid level (Arnett et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…In young lambs, high levels of vitamin A supplementation led to an increase in the total intramuscular lipid level (Arnett et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Pyatt et al (2005) found no correlation (P > 0.10) between marbling score and serum retinol concentration. Arnett et al (2007) showed that marbling score increased in lambs fed 6,600 vs. 0 IU of supplemental vitamin A/kg, and they found a positive correlation (r = 0.30; P < 0.10) between marbling score and serum retinol. Similarly, research conducted to evaluate various vitamin A supplementation and restriction strategies (Gorocica-Buenfil et al, 2007a,b,c, 2008 showed mixed results.…”
mentioning
confidence: 98%